Association of drugs with special caution in the guidelines with falls: A case–control and case–crossover study in Japan. Issue 3 (13th January 2021) - Ishibashi, Yoshiki; Nishitani, Rie; Kato, Takashi; Chiba, Sahoko; Ashidate, Keiko; Ishiwata, Nobuo; Ichijo, Tomoyasu; Sasabe, Masataka
Abstract : Aim: To determine the relationship between multiple medications and falls. Methods: This case–control and case–crossover study was carried out at Kudanzaka Hospital in Chiyoda, Tokyo, Japan. A total of 325 patients who experienced their first falls when hospitalized between January 2016 and November 2018, and 1285 controls matched by sex, age and clinical departments were included in this study. Hospitalization duration and fall risk score were adjusted for in the analyses. Results: In the case–control study, multivariable logistic regression showed that increasing the intake of oral medications was not significantly associated with the incidence of falls (odds ratio 1.02, 95% confidence interval 0.998–1.049). In contrast, drugs prescribed with special caution in accordance with the Elderly Oral Medication Guidelines were significantly associated with falls (odds ratio 1.17, 95% confidence interval 1.09–1.26). A similar pattern was observed in the case–crossover analysis. Among the drugs to be prescribed with special caution according to the guidelines, atypical antipsychotics, non‐benzodiazepine hypnotics and magnesium oxide were significantly associated with the risk of falls. Conclusion: The drugs to be prescribed with special caution according to the guidelines were associated with an increased fall risk. The risk of falls in hospitalized older people due to multiple medications varies among medications. Geriatr Gerontol Int ; : – Geriatr Gerontol Int 2021; : – .